Inclusão de crianças com Transtorno do Espectro Autista (TEA) na educação infantil: práticas pedagógicas, avanços e perspectivas. 2025. - Batista, Raiane Thais de Souza (UNIVERSIDADE ESTADUAL DE PONTA GROSSA - UEPG, 2025)
This study aimed to understand the pedagogical practices, challenges, and perspectives of early childhood teachers working with young children diagnosed with autism in the municipality of Telêmaco Borba, Paraná. The choice of this topic is justified by the increased discussion on school inclusion in Brazil, especially after the enactment of Laws No. 12,764/2012 (Brazil, 2012) and. No. 13,146/2015 (Brazil, 2015), as well as the growing demand for enrollment of children diagnosed with autism in early childhood education. The research was guided by the following question: What pedagogical practices are adopted by early childhood teachers working with young children diagnosed with autism in the municipality of Telêmaco Borba, Paraná? The theoretical framework is based on the contributions of Vygotsky, on social mediation and the importance of context in child development, and on authors of inclusive education, such as Mantoan (2003) and Glat; Pletsch (2012). Bardin's (2016) content analysis guided the organization and interpretation of the emerging categories. This is a qualitative, exploratory, and descriptive study, with data collection conducted through a structured 15-question questionnaire completed by 42 teachers from the 16 Municipal Early Childhood Education Centers (CMEIs) in the second half of 2024. The results indicated advances in the understanding of inclusive education, but also gaps related to continuing education, the availability of adapted pedagogical resources, and interdisciplinary support. Despite educators' dedication, barriers to the full implementation of inclusive practices remain. As a result of this research, two pedagogical resources were developed to support teaching practice and promote meaningful learning, contributing to the construction of a more inclusive and welcoming school environment
Keywords: TEA; Crianças pequenas; Recursos pedagógicos; Estratégias educacionais